Menggagas Pertimbangan Childfree: Pendekatan Multidisiplin dan Interdisiplin - Falah, Mohammad Bachrul; Rohmatuszahroh, Anita Intan (Syakhsiyah Jurnal Hukum Keluarga Islam, 2024)
This research aims to explore childfree considerations from various perspectives involving ecology, macroeconomics and Islamic law. Therefore, a question arises, how is the consideration of childfree from the integration of various disciplines? The framework of the approach used is multidisciplinary and interdisciplinary, so that these disciplines are integrated and connected in the idea of childfree benefits. This research uses library research with a multidisciplinary and interdisciplinary approach. The results showed that ecological considerations regarding childfree revolve around the number of populations that affect the contribution of carbon emission gases. As for the country's economy, it considers the number of populations that affect macroeconomic stability. Islamic law in this context is contextual because childfree considerations are not normative. Such a multidisciplinary approach can be integrated into interdisciplinary. Contextual benefit-based Islamic law uses hifdz an-nafs to see the benefits of childfree in ecology. In addition, hifdz al-mal is used to look at macroeconomic considerations in this context. The ecology and economy of the country integrate with each other to form a balanced and more maslahah consideration between the two. This research contributes to considering the benefits of childfree comprehensively.